2016
DOI: 10.1101/057273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of cryopreservation and post-cryopreservation somatic embryogenesis on the epigenetic fidelity of cocoa (Theobroma cacaoL.)

Abstract: While cocoa plants regenerated from cryopreserved somatic embryos can demonstrate high levels of phenotypic variability, little is known about the sources of the observed variability. Previous studies have shown that the encapsulation-dehydration cryopreservation methodology imposes no significant extra mutational load since embryos carrying high levels of genetic variability are selected against during protracted culture. Also, the use of secondary rather than primary somatic embryos has been shown to further… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Further analysis showed that only 2.6-9.8% of the changes were induced by cryopreservation procedure and the rest were attributed to the in vitro culture processes. In vitro culture-induced DNA methylation was also found in the regenerants recovered from cryopreserved Carica papaya shoot tips [65] and Theobroma cacao somatic embryos [66]. DNA methylation levels were higher in in vitro stock somatic embryos of Theobroma cacao than those regenerated after cryopreservation [66].…”
Section: Epigenetic Integritymentioning
confidence: 85%
See 2 more Smart Citations
“…Further analysis showed that only 2.6-9.8% of the changes were induced by cryopreservation procedure and the rest were attributed to the in vitro culture processes. In vitro culture-induced DNA methylation was also found in the regenerants recovered from cryopreserved Carica papaya shoot tips [65] and Theobroma cacao somatic embryos [66]. DNA methylation levels were higher in in vitro stock somatic embryos of Theobroma cacao than those regenerated after cryopreservation [66].…”
Section: Epigenetic Integritymentioning
confidence: 85%
“…In vitro culture-induced DNA methylation was also found in the regenerants recovered from cryopreserved Carica papaya shoot tips [65] and Theobroma cacao somatic embryos [66]. DNA methylation levels were higher in in vitro stock somatic embryos of Theobroma cacao than those regenerated after cryopreservation [66]. Therefore, the manipulations of in vitro culture procedures, particularly for regeneration via somatic embryogenic, are needed to reduce the probability of alternations in DNA methylation.…”
Section: Epigenetic Integritymentioning
confidence: 97%
See 1 more Smart Citation
“…Because of the recalcitrant (do not survive drying) nature of its seeds, the germplasm of this allogamous tree crop must be conserved in field genebanks as a living collection (Motilal et al ., ) or by cryopreservation (Adu‐Gyamfi and Wetten, ; Adu‐Gyamfi et al ., ). The largest collections of cacao germplasm are those at the International Cocoa Genebank, Trinidad (ICG, T) (https://sta.uwi.edu/cru/index.asp) (2400 accessions) and at the Centro Agronomico Tropical de Investigación y Enseñanza (CATIE) in Costa Rica (https://www.catie.ac.cr/en/) (1146 accessions), with another collection (c. 400 accessions), the International Cocoa Quarantine Centre, housed at the University of Reading, UK (http://www.icgd.reading.ac.uk/icqc/).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, a study conducted by López and co‐workers in 2010 found that de novo genetic mutations and epigenetic modifications do not accumulate with ageing of in vitro induced cacao calli (López et al ., ); this conclusion is also relevant to a recent study of long‐term SE (Quinga et al ., ). Additionally, the SE system has been utilized in cacao germplasm conservation through cryopreservation (Adu‐Gyamfi and Wetten, ; Adu‐Gyamfi et al ., ) and in genetic transformation (Maximova et al ., ; da Silva et al ., ). Induction of cacao somatic embryos has been observed from a range of its tissues, that is zygotic embryos (Pence et al ., ), floral parts—petals and staminodes (Alemanno et al ., , ; Boutchouang et al ., ; Li et al ., ; Tan and Furtek, ), and nucellar tissues (Figueira and Janick, ).…”
Section: Introductionmentioning
confidence: 99%